Psikoedukasi : Stop Bullying Pada Anak-Anak - Ike Utia Ningsih; Fakhriya, Siti Dini (Jurnal Aksi Dosen dan Mahasiswa, 2023)
Bullying is an act committed to hurt others physically, verbally and psychologically. In this activity, a preliminary survey of bullying behavior was conducted and it is known that the understanding of the impact of bullies is still much unknown to children and parents in Purwosari Village. Community service was carried out after discussions with all the KKN students in the village of Purwosari and the village head. Psychoeducation is conducted in order to raise the awareness of adolescents about bullying behavior. The activity starts with a pre-test questionnaire, followed by psychoeducation, and concludes with a post-test questionnaire to determine changes in understanding of bullying. The psychoeducation take place on Sunday, August 13, 2023, starting at 9 a.m. The activity was attended by 16 adolescents in Purwosari Village and was also participated by the village equipment. The Wilcoxon test revealed significant differences in understanding bullying behaviour between pre-test and post-test with sig<0.05. In this case, psychoeducation can be helpful in enhancing adolescents' awareness and understanding of bullying. As the activity concludes, it is meant to help all parties, particularly adolescents, as well as raise awareness and comprehension of bullying behavior